Evaluation of Growth and Feeding Characteristics of Indigenous Chicken Ecotypes of Kenya - Chesoo, Ben K; Nandwa, Anastacia; Wanga, James (African Journal of Education,Science and Technology (AJEST), 2021)
The domestic Indigenous chicken (Gallus gallus domesticus L.) is one of the animal genetic resources that is known to be widespread in Africa. Irrespective of its importance, about 38% poultry population in the world is classified as at risk status. Indigenous chickens (IC) ecotypes exhibit differences in production potentials. The performance of IC ecotypes can be upgraded for economic significance through selection and breeding. However, many of these efforts have not flourished but instead offered new challenges such as amplified cost of production. Eggs of each Kenyan (IC) were collected from the respective AEZ. An on station artificial hatching, growth and feed utilization evaluation was conducted at the University of Eldoret (UoE). Stratigraphic Centurion XVI.I was used for analysis. Highest mean egg weight were from LM ecotype (44.59±3.15 SD) significantly different (P<0.05). Proportions of incubated eggs as well as and those that hatched was the same for all ecotypes (p>0.05). HB ecotype had the lowest proportion of unfertile eggs (p<0.05). A large percentage of eggs with dead embryo came from EM, TR and LM ecotypes. A large fraction of eggs with chicks that were Dead before Hatch came from EM ecotype (38.24%). The average hatching weight of chicks from all ecotypes was positively correlated with egg mean weight. The HB ecotype had the highest weight gain followed by TR ecotype for chicks. HB ecotype had the highest mean weight gain per bird (985.63±154.80) insignificantly different from all other ecotypes assessed (F0.05 (4, 41) =2.29, p=0.0761). There was no significant difference in ADG (g) among ecotypes irrespective (p>0.05). The highest Total Feed Intake per bird in g was recorded in HB (p<0.05). HB ecotype recorded the highest Average Daily Feed Intake (p<0.05). LM ecotype recorded the highest Feed Conversion Ratio of 2.35±0.25 while EM and TR recorded the lowest (p<0.05). In conclusion, the studied indigenous chicken populations in Kenya have demonstrated high variation in egg weight, egg hatchability characteristics and body weight gain as well as reproduction performance between and within ecotypes. This offers a prospect to improve on IC productivity as far as feeding and feed conversion are of concern. In order to conserve IC genetic resources, Molecular characterization and Marker Assisted Selection and breeding towards an efficient feed utilization breeds of indigenous chicken is recommended.